Mechanisms of sympathoexcitation via P2Y6 receptors - Mosshammer, Anna; Zou, Lifang; Boehm, Stefan; Schicker, Klaus (Frontiers in Pharmacology, 2022)
Many drugs used in cardiovascular therapy, such as angiotensin receptor antagonists and beta-blockers, may exert at least some of their actions through effects on the sympathetic nervous system, and this also holds true for e.g. P2Y12 antagonists. A new target at the horizon of cardiovascular drugs is the P2Y6 receptor which contributes to the development of arteriosclerosis and hypertension. To learn whether P2Y6 receptors in the sympathetic nervous system might contribute to actions of respective receptor ligands, responses of sympathetic neurons to P2Y6 receptor activation were analyzed in primary cell culture. UDP caused membrane depolarization and enhanced action potential firing due to current injections in a concentration dependent manner. The excitatory action was antagonized by the P2Y6 receptor antagonist MRS2578, but not by the P2Y2 antagonist AR-C118925XX. UDP raised intracellular Ca2+ in the same range of concentrations as it enhanced excitability and elicited inward currents under conditions that favor Cl- conductances, and these were reduced by a blocker of Ca2+-activated Cl- channels, CaCCInh-A01. In addition, the nucleotide inhibited currents through KV7 channels. The increase in membrane excitability caused by UDP was not altered by the KV7 channel blocker linopirdine, but was enhanced in low extracellular Cl- and was reduced by CaCCInh-A01 and by an inhibitor of phospholipase C. Moreover, UDP enhanced release of previously incorporated [3H]noradrenaline, and this was augmented in low extracellular Cl- and by linopirdine, but attenuated by CaCCInh-A01. Together, these results reveal a sympathoexcitatory action of P2Y6 receptor activation that involves the gating of Ca2+-activated Cl- channels.